(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2019)
Water pollution has been a major problem facing people living in riverine area all over Nigeria. This has become life threaten to majority of people living in the area as well as visitors to the area. A descriptive action research design was adopted foe the study and 3 instruments were developed for the collection of data. The population of the study comprises of all secondary school students in riverine area of Ondo State while 200 respondents were randomly selected from 10 schools 5 on the land and 5 on water. The questionnaire titled Environmental knowledge scale (EKS) Environmental Attitude scale (EAS) AND Environmental practice scale (EPS) were used to collect data for the study. Data generated were analyzed using descriptive statistics of mean, standard deviation and T. test. The result of the study shows that there was significant effect of treatment on participants’ knowledge, attitude and practice towards water pollution and that location of school doesn’t have significant effect on participants’ behavior after the treatment based on the findings, it is therefore recommended that participation programme be encouraged at a level of education for solving environmental problems that is peculiar to any community.